Polyethylene glycol 8000+ citrate salts aqueous two-phase systems: Relative hydrophobicity of the equilibrium phases - Silvério, Sara Isabel Cruz (2016)
The Gibbs free energy of transfer of a methylene group, G*(CH2), is reported as a measure of the relative hydrophobicity of the equilibrium phases. Furthermore, G*(CH2) is a characteristic parameter of each tie-line, and for that reason can be used for comparing different tie-lines of a given aqueous two-phase system (ATPS) or even to establish comparisons among different ATPSs. In this work, the partition coefficients of a series of four dinitrophenylated-amino acids were experimentally determined, at 23 °C, in five different tie-lines of PEG8000(sodium or potassium) citrate ATPSs. G*(CH2) values were calculated from the partition coefficients and used to evaluate the relative hydrophobicity of the equilibrium phases. PEG8000potassium citrate ATPSs presented larger relative hydrophobicity than PEG8000sodium citrate ATPSs. Furthermore, the results obtained indicated that the PEG-rich phase (top phase) has higher affinity to participate in hydrophobic hydration interactions than the salt-rich phase (bottom phase).